Life prediction in multiaxial high cycle fretting fatigue. (May 2020) - Araújo, J.A.; Castro, F.C.; Matos, I.M.; Cardoso, R.A.
Highlights: Multiaxial models can be successfully adapted to estimate fretting fatigue life. New data for Ti-6Al-4V cylinder/plane contact to evaluate wear-based life analysis. Critical distance/plane method yields accurate estimates of fretting fatigue life. Inclusion of wear in the modeling did not significantly improved the life estimates. Elastic-plastic analysis of AA6201-T81 contacting wires improves life estimates. Abstract: The aim of this work is to show that multiaxial fatigue modeling can be successfully adapted to estimate crack initiation life of mechanical assemblies under fretting conditions. The paper is divided into two parts. In Part I, the focus is on the study of size and gradient effects but considering the influence of incorporating fretting wear on the life estimation procedure. New data for a Ti-6Al-4V cylindrical on plane contact configuration were produced to assess the analyses. It is shown that critical plane criteria, coupled with a critical distance which varies with life, are capable to provide accurate estimates of fretting fatigue life in the medium high cycle regime. The inclusion of wear in the modeling did not significantly improved the life estimates but increased a lot the computational cost. In Part II, the paper extended this life estimation approach to the contact of wires taken from overhead conductors. Fretting fatigue data of AA1350-H19 wires and new tests on the more resistant AA6201-T81 corroborated the successful use of the life methodology to other materials and applications.